Early cessation of breastfeeding amongst women in South Africa: an area needing urgent attention to improve child health - Doherty Tanya; Sanders David; Jackson Debra; Swanevelder Sonja; Lombard Carl; Zembe Wanga; Chopra Mickey; Goga Ameena; Colvin Mark; Fadnes Lars T; Engebretsen Ingunn MS; Ekström Eva-Charlotte; et al. (BMC, 2012)
Abstract Background Breastfeeding is a critical component of interventions to reduce child mortality. Exclusive breastfeeding practice is extremely low in South Africa and there has been no improvement in this over the past ten years largely due to fears of HIV transmission. Early cessation of breastfeeding has been found to have negative effects on child morbidity and survival in several studies in Africa. This paper reports on determinants of early breastfeeding cessation among women in South Africa. Methods This is a sub group analysis of a community-based cluster-randomized trial (PROMISE EBF) promoting exclusive breastfeeding in three South African sites (Paarl in the Western Cape Province, and Umlazi and Rietvlei in KwaZulu-Natal) between 2006 and 2008 (ClinicalTrials.gov no: NCT00397150). Infant feeding recall of 22 food and fluid items was collected at 3, 6, 12 and 24 weeks postpartum. Women's experiences of breast health problems were also collected at the same time points. 999 women who ever breastfed were included in the analysis. Univariable and multivariable logistic regression analysis adjusting for site, arm and cluster, was performed to determine predictors of stopping breastfeeding by 12 weeks postpartum. Results By 12 weeks postpartum, 20% of HIV-negative women and 40% of HIV-positive women had stopped all breastfeeding. About a third of women introduced other fluids, most commonly formula milk, within the first 3 days after birth. Antenatal intention not to breastfeed and being undecided about how to feed were most strongly associated with stopping breastfeeding by 12 weeks (Adjusted odds ratio, AOR 5.6, 95% CI 3.4 - 9.5 and AOR 4.1, 95% CI 1.6 - 10.8, respectively). Also important was self-reported breast health problems associated with a 3-fold risk of stopping breastfeeding (AOR 3.1, 95%CI 1.7 - 5.7) and the mother having her own income doubled the risk of stopping breastfeeding (AOR 1.9, 95% CI 1.3 - 2.8). Conclusion Early cessation of breastfeeding is common amongst both HIV-negative and positive women in South Africa. There is an urgent need to improve antenatal breastfeeding counselling taking into account the challenges faced by working women as well as early postnatal lactation support to prevent breast health problems.